CLAVE PARA LA SELECCION DE TEXTOS ESCOLARES ESPECIALMENTE EN BIOLOGIA - BELTRAN, ENRIQUE (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1947)
The different cellular elements of the medulla oblongata of the guinea pig are described histologically, reference is made to their variations from the human, and a scheme for their classification is suggested
REV SOC MEX HIST NAT
Keywords: CLAVE, SELECCIÓN, TEXTOS ESCOLARES, BIOLOGIA; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL (ZOOLOGIA); ESTUDIO Y ENSEÑANZA